Pengaruh Mutasi terhadap Kinerja Pegawai di Dinas Perumahan Rakyat dan Kawasan Permukiman Kota Tasikmalaya - Muhamad Fardiansyah (Fenery Library, 2021)
Mutation of employees in an organization is a routine activity in an effort to provide refreshment for employees by moving from one job to another, as well as to provide opportunities to develop abilities with better work results. The statement of this research that the performance of employees at the Department of Public Housing and Settlement of Tasikmalaya City is influenced by mutations. As for the purpose of this study is to determine the effect of mutations on the performance of employees in the Department of Public Housing and Settlement Areas of the City of Tasikmalaya. The research method used in this research is quantitative research methods with a descriptive approach. Respondents in the study were employees of the Public Housing and Settlement Areas of Tasikmalaya City. The data collection technique is done through observation and using a questionnaire. The data analysis technique in this study was carried out through multiple regression tests, to determine the magnitude of the influence of the variables under study, while to determine the size of the effect partially, it was carried out using path analysis formulations. Based on the results of the study, it shows that simultaneous or joint mutations affect the performance of employees at the Department of Public Housing and Settlement of the City of Tasikmalaya which is determined by the principles of transfer of functions, transfer of responsibilities, and transfer of status. From the results of data testing, each aspect of this research study, which consists of the principle of transferring functions, the principle of transferring responsibility, and the principle of transferring status jointly affect the performance of employees at the Department of Public Housing and Settlement Areas of Tasikmalaya City.